Analysis of the epidemiological profile in oral health in different regions of the Municipality of Penedo –AL: Strategy for strengthening and redirecting oral health policy (Research, Society and Development, 2021)
Conducting epidemiological surveys is an important tool for understanding the prevalence of oral diseases and, thus, being able to guide the planning, execution and evaluation of health actions in a population. Thus,a cross-sectional study was carried out with 13.706 people, living in the rural and urban areas, aged 0-60 years, who were classified according to the risk of caries, evaluated in: 1(low); 2 (medium), 3 (high), contributing factors for oral cancer, need and use of dental prosthesis and prevalence of periodontal diseases. The data were tabulated and submitted to descriptive and Kappa analysis with intra and inter-rater agreement of 100% and 95%, respectively. There was a greater number of individuals classified as risk 1 and 2 in the urban area. In the contributing factors for oral cancer exposure to smoking and alcohol consumption was similar in the populations analyzed. The use of prostheses, the rural area (27%) stood out in relation to the urban area (18.2%), with the age group of 20-59 years being most committed by patients with the use of dental prosthesis. The prevalence of changes in the mucosa in the same group (20-59 years) was a prominent factor between the two regions, with the rural area 6.2% and the urban area 2.8%. As for the development of periodontal disease it was found that the urban area stood out in relation to the rural area, with 25.13% of individuals with active disease. Such results suggest better targeting of oral health policies and their care strategies, in order to achieve access to the dental service and resolution based on the specificities of different age groups and locations.